Theory of knowledge classical and contemporary readings - Pojman, Louis P (Wadsworth Pub., 1999)
Pojman's THE THEORY OF KNOWLEDGE: CLASSIC AND CONTEMPORARY READINGS is nothing less than the most up-to-date and comprehensive reader in knowledge theory on the market. Containing 63 readings, the book is now organized into eleven parts that outline the subjects' central to contemporary epistemology. Opposing positions are set forth for all issues and a brief synopsis introduces each reading.